Cloning and Expression of Mycobacterium tuberculosis and Mycobacterium leprae Dihydropteroate Synthase in Escherichia coli - Nopponpunth, Vanida (American Society for Microbiology, 1999)
The genes for dihydropteroate synthase of Mycobacterium tuberculosis and Mycobacterium leprae were isolated by hybridization with probes amplified from the genomic DNA libraries. DNA sequencing revealed an open reading frame of 840 bp encoding a protein of 280 amino acids for M. tuberculosis dihydropteroate synthase and an open reading frame of 852 bp encoding a protein of 284 amino acids for M. leprae dihydropteroate synthase. The dihydropteroate synthases were expressed under control of the T5 promoter in a dihydropteroate synthase-deficient strain of Escherichia coli. Using three chromatography steps, we purified both M. tuberculosis and M. leprae dihydropteroate synthases to >98% homogeneity. Sodium dodecyl sulfate-polyacrylamide gel electrophoresis revealed molecular masses of 29 kDa for M. tuberculosis dihydropteroate synthase and 30 kDa for M. leprae dihydropteroate synthase. Gel filtration of both enzymes showed a molecular mass of ca. 60 kDa, indicating that the native enzymes exist as dimers of two identical subunits. Steady-state kinetic parameters for dihydropteroate synthases from both M. tuberculosis and M. leprae were determined. Representative sulfonamides and dapsone were potent inhibitors of the mycobacterial dihydropteroate synthases, but the antimycobacterial agent p-aminosalicylate, a putative dihydropteroate synthase inhibitor, was a poor inhibitor of the enzymes.